STEMM-Humanities Co-Teaching and the Humusities Turn - Hella B Cohen (Journal of the Assembly for Expanded Perspectives on Learning, 2020)
Donna Haraway calls for a new Humanities that attends to the role of this traditionally anthropocentric field on a damaged planet. The Humusities, she offers, empower us to teach at the intersections of observation, speculation, and affective reasoning. This article considers co-teaching and interdisciplinary teaching structures as part of the Humusities model. Drawing from interviews and pedagogical materials of professors who have co-taught STEMM-Humanities classes, student feedback from these sections, and current research on interdisciplinary education, I theorize the possibilities and limitations of the interdisciplinary Humusities at the undergraduate level. The article explores how we translate the tenets of Haraway into a co-taught curriculum, while considering the objectives, benefits, and drawbacks of doing so. Several pedagogical and procedural issues are discussed: “norming” student performance in courses where two or more instructors are likely using different assessment modalities; navigating STEMM-Humanities co-teaching within current university budget structures; considering how university size and collegial climate affects implementation; and revealing roadblocks that exist relating to Registrar policy, enrollments, student majors, and hiring practices. I also speculate how the Humusities turn can redistribute university wealth and mitigate educational threats at the state and federal levels. Like science fiction in Haraway’s Staying with the Trouble, co-teaching across the Humusities engages in “storytelling and fact telling; it is the patterning of possible worlds and possible times, material-semiotic worlds, gone, here, and yet to come” (31). With this sentiment in mind, I explore what is entailed in the process of humanizing STEMM and composting the humanities.
Keywords: Humusities; STEMM; Humanities